Kajian Model Demokrasi : Teori dan Paradigma - Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2021)
The meaning and substance of a democratic system is government from, by, and for the people. In a (relatively) rather broad sense, democracy is often interpreted as a government with all the activities that are managed, carried out by making the people as the subjects and fulcrums of determining the running of politics and governance. Because democracy is a system that is based on the people's sovereignty, nihilism towards elite sovereigns, or party sovereigns, or state sovereigns, or military sovereigns must be removed. This paper discusses the theories and paradigms of democratic models, including; (1) classical democratic models; (2) procedural democracy; (3) pluralist democracy; (4) autonomy democracy; (5) consensus or consosiational democracy; (6) deliberative democracy; and finally (7) social democracy.